Mengupayakan Keluarga yang Harmonis - Christofora Megawati Tirtawinata (Bina Nusantara University, 2013)
Harmonious family is the best environment for individuals to be able to shape a healthy personality. Healthy personality and healthy families are necessary in building a healthy society, which in turn is needed in building the nation. In fact many couples have not been able to seek a harmonious family so that they end their marriages in divorce. Causes of divorce in general are because there is no harmony. Article is based on the observation and study of literature. It describes the efforts to build harmony in the family, before marriage and during marriage. Therefore, the couple is able to understand the difference between them and respond positively and always communicate assertively.